Study on Diabetic Retinopathy Detection Techniques - Faisal, KK; Deepa, CM; Nisha, SM; Gopi, Greeshma (International Journal of Computer Sciences and Engineering, 2025)
Diabetic Retinopathy (DR) also known as diabetic eye disease. It is the damage occurs to the retina due to diabetes. It can eventually lead to blindness. So the early detection of disease is needed, Manual detection is time consuming and often make observation error. Hence several computer-aided systems are introduced and which would make fast and consistent diagnosis- aid useful for biomedical and health informatics field. The Diabetic retinopathy detection methods that uses machine learning techniques. In one system classifiers such as the Gaussian Mixture model (GMM), k-nearest neighbor (kNN), support vector machine (SVM) are used and another system that uses GMM, kNN, SVM, and combinational classiﬁers are used for classifying retinal fundus images.